Ureditev domačega okolja starostnikov za preprečevanje padcev - Shagaeva, Elena (Šport (Ljubljana), 2024)
A systematic literature review was conducted to analyse the evidence on the impact of home adaptation on reducing the risk of falls in older people. The study population included older people aged 60 years and over living in a home environment, including those with comorbidities such as dementia, cognitive impairment, visual impairment and functional decline. The interventions included a home environment risk assessment using different tools such as WeHSA and Home- FAST. In addition to adaptations, some studies included balance and strength training programmes. The heterogeneity of the results of the studies reviewed does not allow a single conclusion to be drawn on the effectiveness of adaptations to the home environment in preventing falls among older people.
Keywords: active aging; aging; aktivno staranje; elderly; environmental adaptation; ergonomija doma; fall prevention; falls; home ergonomics; older adults; padci; preprečevanje padcev; prilagoditev okolja; safety recommentations; sport; staranje; starejši odrasli; starostnik; šport; varnostna priporočila